2022
DOI: 10.1186/s43058-022-00320-3
|View full text |Cite
|
Sign up to set email alerts
|

Management strategies to de-implement low-value care—an applied behavior analysis

Abstract: Background There is a lack of knowledge about management strategies being used to de-implement low-value care (LVC). Furthermore, it is not clear from the current literature what mechanisms are involved in such strategies and how they can change physicians’ behaviors. Understanding the mechanisms is important for determining a strategy’s potential impact. Applied behavior analysis focuses on processes involved in increasing and decreasing behaviors. Therefore, the aim of this study is to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…One challenge in de-implementation of LVC is that few practices are LVC for all patients (7,50). For example, ordering an x-ray for patients who are being referred for surgery is still appropriate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One challenge in de-implementation of LVC is that few practices are LVC for all patients (7,50). For example, ordering an x-ray for patients who are being referred for surgery is still appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…From a theoretical perspective, the strategies were designed to reinforce and thereby increase one behavior and, as a result, lead to a decrease in another, so-called differential reinforcement (28). Differential reinforcement has been suggested for use in de-implementation (44) but has rarely been used (50,51). However, the participants emphasized that to target the dilemma of few LVC practices being LVC for all patients, approaches are necessary that improve a behavior's precision so it is only present during the right set of circumstances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, clinicians are influenced both by individual factors and by factors in the wider healthcare system to provide LVC, which highlights the importance of working strategically at different levels in the healthcare system to reduce LVC [7,11]. This is supported in a recent Swedish study which found that both local strategies and systemic strategies are likely required to deimplement LVC in primary healthcare in Sweden [12].…”
Section: Introductionmentioning
confidence: 97%